2007
DOI: 10.1097/01.inf.0000261927.90189.88
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effect of Chlorhexidine Skin Cleansing on Skin Flora of Neonates in Bangladesh

Abstract: Chlorhexidine skin treatment produced more extended skin cleansing effects than the placebo treatment. It is possible that the quantitative and qualitative reductions observed in the skin flora might contribute to reducing neonatal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
2
33
2
3
Order By: Relevance
“…Similar results have been reported from other studies too. 8,20 The results are, however, in contrast with the observation by Garland et al, 11 who found localized contact dermatitis after the use of chlorhexidine-gluconate impregnated dressing and hence were not in favor of its prolonged use in LBW infants. Unlike the antimicrobial dressing, single skin cleansing does not lead to prolonged exposure, and hence is unlikely to result in severe local reactions in these infants.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Similar results have been reported from other studies too. 8,20 The results are, however, in contrast with the observation by Garland et al, 11 who found localized contact dermatitis after the use of chlorhexidine-gluconate impregnated dressing and hence were not in favor of its prolonged use in LBW infants. Unlike the antimicrobial dressing, single skin cleansing does not lead to prolonged exposure, and hence is unlikely to result in severe local reactions in these infants.…”
Section: Discussioncontrasting
confidence: 56%
“…22 The study from Bangladesh that evaluated single skin cleansing with chlorhexidine also showed a significant reduction in the positive culture rates until three days after the intervention. 20 In contrast, the study from Nepal showed reduction in the colonization rates at 2 h but not at 24 h. 8 In this study, skin cleansing with 0.25% chlorhexidine was found to reduce the risk of axillary colonization by almost 60% at 24 h when compared with no cleansing. The incidence of skin colonization at 72 h was, however, not different between the two groups.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…9,10,17,18 A similar study was done in Bangladesh (2007) attempting to study the extended cleansing effects of 0.25% chlorhexidine. Their skin colonization rates seem comparable to be to us.…”
Section: Discussionmentioning
confidence: 99%